How to be a blogger and vlogger in 10 easy lessons - Birley, Shane, ....- (London : Marshall, 2016)
In this new addition to the Super Skills series, children can master a new digital talent--creating blogs, vlogs, and podcasts--in 10 easy lessons! Each stage is fully illustrated with step-by-step illustrations and photographs, so children can learn 10 key skills to develop and promote an exciting new online blog or vlog. Along with professional tips and practical techniques, this book will help young readers become expert bloggers in no time. From planning what to share with the world to learning how to stay safe online, this book leads the way.
Keywords: Bloggen; Vloggen